2000
DOI: 10.1046/j.1525-1438.2000.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of cell cycle proteins and genomic instability in borderline, early and advanced stage ovarian carcinomas

Abstract: Disturbed cell cycle-regulating checkpoints and impairment of genomic stability are key events during the genesis and progression of malignant tumors. We analyzed 80 epithelial ovarian tumors of benign (n = 10) and borderline type (n = 18) in addition to carcinomas of early (n = 26) and advanced (n = 26) stages for the expression of Ki67, cyclin A and cyclin E, p21WAF-1, p27KIP-1 and p53 and correlated the results with the clinical course. Genomic instability was assessed by DNA ploidy measurements and, in 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…The findings we describe for Mcm-2 are similar to those obtained in previous studies using Ki67 (Garzetti et al, 1995;Blegen et al, 2000). Indeed, it has been shown previously that tumour cell proliferation, as assessed by the Ki67 LI, was significantly higher in cases of serous ovarian cystadenocarcinoma that recurred or progressed than in those that did not (Garzetti et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…The findings we describe for Mcm-2 are similar to those obtained in previous studies using Ki67 (Garzetti et al, 1995;Blegen et al, 2000). Indeed, it has been shown previously that tumour cell proliferation, as assessed by the Ki67 LI, was significantly higher in cases of serous ovarian cystadenocarcinoma that recurred or progressed than in those that did not (Garzetti et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…There are different opinions concerning the histogenesis of serous ovarian tumors, some supporting a progression from SBT to SAC [8,10] and others favoring a dualistic model [5,[11][12][13][14]. We studied this issue using high-resolution DNA ploidy image analysis in different subgroups of SBT and grades of SAC in a large and well-characterized retrospective material.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin E is overexpressed in 18-70% of EOCs, and is more often detected in clear cell carcinoma than in other histological types [74,84,94,[104][105][106][107][108][109][110][111] (Table 3(b)). Most authors showed that high-cyclin E expression represents a poor prognostic variable [84,94,106,107,109,111,112].…”
Section: Cyclin Ementioning
confidence: 99%
“…Most authors showed that high-cyclin E expression represents a poor prognostic variable [84,94,106,107,109,111,112]. For instance, Sui et al [107] reported a lower survival in women who had cyclin E overexpression than in those who had not.…”
Section: Cyclin Ementioning
confidence: 99%